Discriminatory power of trabeculectomy bleb internal reflectivity and morphology in surgical success using anterior segment optical coherence tomography - Jeremy C.K. Tan; Matthew Roney; Matteo Posarelli; Abdus Samad Ansari; Mark Batterbury; Neeru A. Vallabh (BMC Ophthalmology, 2025)
Abstract Background The post-operative evaluation of trabeculectomy blebs has traditionally relied on subjective clinical grading systems performed at the slit-lamp. This study explores the use of swept source anterior-segment optical coherence tomography (AS-OCT) to objectively measure bleb internal reflectivity and morphology, and to distinguish blebs with surgical success vs. failure. Methods Cross-sectional study of patients with glaucoma who had undergone trabeculectomy at least one year prior. Swept source AS-OCT was used to capture filtering blebs in the sagittal plane. Standardised regions of interests on the sagittal plane were segmented, and pixel intensity values and bleb height were measured. Receiver operating characteristic curves were used to examine the discriminatory ability of pixel intensity values and bleb morphology to classify blebs with surgical success or failure. Results 100 eyes of 65 patients were included, with a median post-operative follow up of 7.0 years (IQR 3.2–16 years). The proportion of complete success, qualified success and failure was 45%, 33%, and 22% respectively. The maximum bleb height was significantly greater in the blebs with complete success (1.74 vs. 1.25 vs. 1.23 mm in CS vs. QS vs. F, one-way ANOVA, p < 0.0001). Mean pixel intensity was significantly lower in blebs with complete success (150.8 vs. 157.4 vs. 167.4 in CS vs. QS vs. F, p = 0.0001). Bleb intensity standard deviation (AUC 0.81), maximal bleb height (AUC 0.76), mean pixel intensity (AUC 0.75) and minimum pixel intensity (AUC 0.75) offered the best discrimination between surgical success and failure. Conclusions Swept-source AS-OCT can be used to quantify bleb internal reflectivity and morphology, which can be used to distinguish between well vs. poorly functioning blebs. These parameters may assist surgeons in the objective evaluation of post-operative bleb outcomes.